PEMANFAATAN BUAH TOMAT (Solanum Lycopersium) SEBAGAI BAHAN TAMBAHAN DALAM PEMBUATAN PERMEN JELLY - Yulianti, Yulianti; Syam, Husain; Sukainah, Andi (Universitas Negeri Makassar, 2018)
This study aims to know the concentration the most of panelists preferredÂ when organoleptik test, knowing the water content and vitamin C content on jelly candy. This research is a quantitative research (experiment) with Completely Randomized Design (RAL) one factor with 3 treatments conducted as many as 3 times replications. The analytical technique used in this study is the analysis of variance analyzed using SPSS version 22. The results showed that for the color, texture, aroma and taste most preferred by the panelist that is on the treatment of A with concentration fruit sari of tomato 200g, the best of treatment at content of water with addition of fruit sari 200gÂ and vitamin C content with the addition of 300g.